Development of diarylpentadienone analogues as alpha-glucosidase inhibitor: Synthesis, in vitro biological and in vivo toxicity evaluations, and molecular docking analysis - Maryam Aisyah, Abdullah; Lee, Yu-Ri; Siti Nurulhuda, Mastuki; Leong, Sze Wei; Wan Norhamidah, Wan Ibrahim; Muhammad Alif, Mohammad Latif; Aizi Nor Mazila, Ramli; Mohd F. F., Mohd Aluwi; Siti Munirah, Mohd Faudzi; Kim, Cheol-Hee (Academic Press Inc., 2020)
A series of aminated- (1–9) and sulfonamide-containing diarylpentadienones (10–18) were synthesized, structurally characterized, and evaluated for their in vitro anti-diabetic potential on α-glucosidase and DPP-4 enzymes. It was found that all the new molecules were nonassociated PAINS compounds. The sulfonamide-containing series (compounds 10– 18) selectively inhibited α-glucosidase over DPP-4, in which compound 18 demonstrated the highest activity with an IC50 value of 5.69 ± 0.5 µM through a competitive inhibition mechanism. Structure-activity relationship (SAR) studies concluded that the introduction of the trifluoromethylbenzene sulfonamide moiety was essential for the suppression of αglucosidase. The most active compound 18, was then further tested for in vivo toxicities using the zebrafish animal model, with no toxic effects detected in the normal embryonic development, blood vessel formation, and apoptosis of zebrafish. Docking simulation studies were also carried out to better understand the binding interactions of compound 18 towards the homology modeled α -glucosidase and the human lysosomal α -glucosidase enzymes. The overall results suggest that the new sulfonamide-containing diarylpentadienones, compound 18, could be a promising candidate in the search for a new α-glucosidase inhibitor, and can serve as a basis for further studies involving hit-to-lead optimization, in vivo efficacy and safety assessment in an animal model and mechanism of action for the treatment of T2DM patients.